(untitled) (World Bulletin of Social Sciences, 2025)
The lexical meaning of words plays a critically important role in the translation process. Understanding the meanings of words, their context, and cultural nuances is essential for achieving accuracy and adequacy in translation. The article examines the main aspects of lexical meaning, its types, and its influence on translation decisions. It also discusses the problems arising from polysemy, synonymy, and cultural differences. Examples from translation practice are provided to illustrate the presented concepts.